Telaah Kritis terhadap Fungsionalitas Gereja Toraja Berdasarkan Kritik Sosio-Religi Karl Marx - Yakob Sampe Rante (Mahesa Research Center, 2021)
This study aims to critique and evaluate the church's functionality, namely the church in its social function. The Toraja Church is still not here to carry out its real social function. As a result, various kinds of social injustice that are produced from culture settle right within the sphere of the church. The church exists only as a producer of the imagination: directing the imagination, without fixing problems on earth. This study uses a qualitative method with a literature observation approach. As a basis, the theory used in this research is Karl Marx's socio-religious criticism theory. The essence of this criticism is not rejection of religion, but rejection of religious practices which merely produce illusions, so as not to solve the problems experienced by society, especially Christians, as a result, society becomes alienated. The Toraja Church is required not to solve problems through imagined solutions, but instead to bring concrete liberating solutions in society. The church should be a real medicine where there is a sick soul due to the chaos of the world. With the revival of church functionality, the church has become a strong fortress for the community towards peace.